2000
DOI: 10.5694/j.1326-5377.2000.tb123871.x
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between use of proton pump inhibitors and prescribing guidelines

Abstract: Objective To determine (i) the relationship between prescriptions for proton pump inhibitors (PPIs) and upper gastrointestinal conditions, and (ii) compliance with Pharmaceutical Benefits Scheme (PBS) prescribing guidelines for PPIs. Design Drug utilisation evaluation. Setting 800‐bed metropolitan teaching hospital. Participants 253 patients dispensed PPIs from the hospital pharmacy over five consecutive weeks (11 January to 15 February 1999). Main outcome measures Recorded gastrointestinal conditions; previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…In total, 72% of patients were considered to have undergone appropriate investigation before commencing a proton pump inhibitor. A recent study in Brisbane also found that 72% of patients were investigated appropriately before a proton pump inhibitor was commenced (30).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 72% of patients were considered to have undergone appropriate investigation before commencing a proton pump inhibitor. A recent study in Brisbane also found that 72% of patients were investigated appropriately before a proton pump inhibitor was commenced (30).…”
Section: Discussionmentioning
confidence: 99%
“…Two-thirds of the patients prescribed PPI therapy in our study had not undergone upper GI endoscopy. Newton et al (8) found that one quarter of their patients had been prescribed PPI therapy with no prior investigation compared with 28% in the study by Pillans et al (7). Naunton et al (9) found that endoscopy had been performed in only 54% of patients prior to commencing PPI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The standard prescribed daily dose of omeprazole is 20 mg, but over 30% of our patients on omeprazole were prescribed 40 mg daily. In their survey of hospital prescribing, Pillans et al (7) found that the prescribed daily dose of omeprazole was more than 20 mg in 39% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests PPIs are often overused. [3][4][5][6][7][8] PPIs are not without their side effects (diarrhoea, headache in up to 10%), and studies have linked the use of PPIs to an increased risk of community acquired pneumonia, 9 10 C difficile diarrhoea, [11][12][13] and Campylobacter jejuni gastroenteritis. 14 PPIs also have interactions with many drugs 15 and can occasionally cause severe adverse reactions such as hepatic, renal, skin, and bone marrow toxicity and anaphylaxis.…”
mentioning
confidence: 99%